Intelligent technique for mining customers review by the help of opinion mining (International Journal of Engineering and Computer Science, 2017)
In the work an intelligent technique will develop to analyze and summarize the customer comment with the help of opinion mining and the part of speech tagging. Comments made by the customers some times are not able to understand by the computer so easily , so the intelligent technique help to overcome this problem that any web based business will become so easy and transparent to both customers and merchants. In the proposed work with the help of several steps like feature identification, sentiment analysis, and Summarization the orientation of each comment can be checked and user can know whether the comment is in favour or in against of the product